Adverse Drug Reactions in Paediatric In-Patients in a South African Tertiary Hospital. (13th December 2018) - Makiwane, Memela; Decloedt, Eric; Chirehwa, Maxwell; Rosenkranz, Bernd; Kruger, Mariana
Abstract: Background: The prevalence of adverse drug reaction (ADR) rates in children in sub-Saharan Africa is unknown. Objectives: To describe the prevalence of ADRs in paediatric in-patients at a tertiary hospital in South Africa. Methods: This is a prospective study during a 3-month study period. Data collected included age, sex, diagnosis, medicines received and ADRs experienced. Causality were assessed, using the 10-question Naranjo probability scale and classified according to the Hartwig severity scale. Results: There were 61 ADRs in 18.4% (52 of 282) of patients. Median age of patients was 1.4 years (interquartile range: 0.5–5.3 years). ADR was the primary admission reason in 31%. The majority of the ADRs were moderate 45.9% (28 of 61), and only 11.5% severe (7 of 61). Paediatric oncology patients suffered significantly more ADRs (56.5%; 13 of 23) [odds ratio 7.3 (3.0–17.9), p  < 0.01], followed by HIV-infected patients (42.9%; 9 of 21). Conclusion: The prevalence of ADRs was 18.4%, while 31% was the reason for admission.